Eating in the dark – an ethical appraisal of genetically modified foods’ - Early, Janet (My University, 2011)
Science can define what is practicable, what can be done, but it cannot determine which developments it is right to pursue- this is largely an ethical judgment attempting to answer ‘ought we to do it’? The most sensible approach to making an ethical assessment is to try and weigh up the benefits of a novel technology against its potential to do harm. Deciding whether GM technology is acceptable in ethical terms involves a judgment about both the plausibility and moral weight of competing sets of claims, beginning with an assessment of the possible benefits and risks. Using four main guiding principles as the basis of my discussion and point of evaluation, I focus firstly on the principle of general welfare to examine the debate what would amount to an adequate safety assessment of GM foods and its possible ecological risk. The right of consumers to freedom of choice is addressed by exploring both the arguments against and for labelling. The principle of justice then questions the claims whether food security can indeed be improved by using GM technology and how patents, bioprospecting and biopiracy can be judged ethically justifiable. Finally the ethical status of the natural world is raised by attempting to answer whether modern biotechnology could be considered blasphemous and whether it is ethically permissible to breach the natural integrity of the species. Using these guiding principles do not make such as assessment straightforward as they cannot be rigidly applied in an abstract way to reflect absolutes on what is right or wrong and their operation depends on context. My approach is normative and presented in a way to stimulate dialogue as an explorative ethical travel through the genetically modified zone with the recognition that the debate remains inconclusive and controversial. Keywords: GM; Genetically Modified Foods; GM Technology; Transgenic.
Keywords: Genetically modified foods--Moral and ethical aspects; Bioethics